An operations research and systems analysis study of weighing scales used for growth surveillance. - Raneses, Nestor O.
Weight is the accepted indicator of growth in the growth monitoring system in the Philippines. The right choice and correct use of the appropriate weighing instrument or scale is of paramount importance for procuring accurate weight during weight surveillance (Operation Timbang). This operations research and systems study evaluates the different weighing scales used in the field, examines the different factors causing inaccuracies in weighing, investigates the feasibility of locally manufacturing the required weighing scales, and scrutinizes the calibration, maintenance and procedure needs of the recommended weighing scales. Seventy eight (40 Rural Health Units and 38 Barangay Health Stations) health stations in Marikina, Quezon City, Pangasinan and Cavite were surveyed. The bar scale, the Salter spring type weighing scale, the adult clinical scale and the bathroom scale were found to be the most commonly used weighing instruments. Calibration, maintenance and proper use were generally observed to be wanting and inadequate. The study recommends the phase out of the bathroom scale; the use of the Salter spring type; the infant beam scale and the bar scale when weighing in the field; and the use of adult clinical scale or beam type clinical scale at health stations. It further recommends the standardized regular calibration and maintenance procedure for all scales used in growth monitoring. All procedures are recommended to be in simple instructional form. For calibration, the use of standard test weights is recommended. The study finally recommends a modified weighting scale and crib design and the establishment of a regular replacement cycle for these weighing instruments. The local manufacture of weighing scale was found to be feasible.